A dynamic information platform for underground coal mine safety based on internet of things. (March 2019) - Wu, Yaqin; Chen, Mengmeng; Wang, Kai; Fu, Gui
Highlights: A dynamic information platform for underground coal mine is established. The platform includes six layers. Two coal mines are chosen as practical examples. Big data and cloud computing techniques are used in the IoT platform. Abstract: Mechanical and intelligent mining technology reduces labor intensity, accidents and casualties while improving mining efficiency in underground coal mines. Such advanced mining methods are gradually realized in China with increasing application of an Internet of Things (IoT) technique. In this study, a dynamic information platform is established for underground coal mine based on IoT technology. The platform aims to satisfy various objectives of potential users through combining four subsystems, including data acquisition, transmission, analyzation and application systems. To achieve such functions, six functional layers are composed of the platform, including the supporting layer, perception layer, transmission layer, service layer, data extraction layer and application layer. The platform can monitor and record working conditions data of the coal mine production systems as well as location information of underground equipment and miners. Based on cloud computing techniques, big data related to underground coal mining can be analyzed quickly, and critical data associated with user requirements can be extracted precisely. The platform provides a 3D virtual mine system, safety diagnosis system, safety inspection system and emergency rescue system for coal mines. With the established platform, the danger-spotting and subsequent decision-making capabilities of users can be greatly enhanced to ensure underground mining safety.